A finite element simulation of MOM (metal‐on‐metal) hip implant. (16th January 2019) - Chaturvedi, Sumita; Bharti, Prem Kumar; Yadav, Saurabh Kumar; Singh, Saumya
Abstract: The entire load in human body is supported by the hip joint bearing. In the present work, elastohydrodynamic lubrication analysis of metal and metal hip implant is performed by using Newtonian lubricant. The Reynolds equation coupled with stress equilibrium equation has been used to get the pressure and performance characteristics of hip joint bearing. The governing Reynolds equation is nonlinear and cannot be solved by using close form solution methods. The finite element method and Newton‐Raphson method are used to obtain solution of the present equation. It has been observed that numerical convergence is much faster with NR method. From the results, it is observed that FEM with modified Newton‐Raphson method has the capability to compute accurate results for realistic modelling.